Evaluation of intraperitoneal splash block by lignocaine and ropivacaine on stress parameters in dogs undergoing keyhole ovariohysterectomy - Ansari, Md. Moin; Shafi, Alisa; Makhdoomi, D.M.; Nabi, Showkatul (Indian Journal of Veterinary Surgery, 2026)
The study evaluated the effects of splash block using local anaesthetic agents - lignocaine, ropivacaine, and their combination - on surgical stress and the associated alterations in oxidative and antioxidant parameters following keyhole ovariohysterectomy (OHE) in 24 intact bitches. The dogs were randomly allocated into four groups, receiving intraperitoneal administration of either normal saline (0.5 mL/kg), 2% lignocaine hydrochloride (2 mg/ kg), 0.5% ropivacaine hydrochloride (3 mg/kg), or a combination of both drugs at the same concentrations and dosages. The splash block was applied before closure of the muscle layer to assess its influence on oxidant markers such as lipid peroxidation (LPO) and antioxidant parameters including catalase (CAT), superoxide dismutase (SOD), and glutathione (GSH). The parameters were recorded at 0, 24, and 48 hours. Lipid peroxidation (LPO) increased at 24 hr and declined by 48 hr, although the values did not return to baseline (0-hr) levels. Group D exhibited significantly lower LPO values at all-time intervals compared to the other groups. Catalase (CAT), an enzymatic antioxidant, showed a reduction at both 24 and 48 hr, with no significant difference between these two time points, and no notable variation among the treatment groups. Superoxide dismutase (SOD) levels decreased significantly at 48 hr, again with no significant differences among groups. Glutathione (GSH) values gradually declined from 0 to 48 hr, with no significant intergroup variation. Overall, the findings indicate that intraperitoneal administration of 2% lignocaine HCl and 0.5% ropivacaine HCl as a splash block may be beneficial as part of a multimodal approach to pain management and reduction of surgical stress following OHE in dogs.